EFEKTIVITAS BEKAM DALAM MENURUNKAN FREKUENSI SERANGAN VERTIGO PADA PASIEN NY. A DI KLINIK ZEIN HOLISTIK - Serliana Bine; Samsualam; Eliati Paturungi; Sunarti (Jurnal Kesehatan, 2025)
Vertigo is often accompanied by headaches that interfere with daily activities and reduce the patient's quality of life. Non-pharmacological management such as cupping therapy is increasingly used as an effort to reduce pain and vertigo complaints. A nursing care approach with SDKI, SIKI, and SLKI standards is needed to provide a systematic and measurable intervention The purpose of this study is to determine the picture of nursing care in patients with Acute Pain problems using SDKI, SIKI, and SLKI standards, as well as the effectiveness of cupping interventions in reducing pain intensity. This study used a case study method on a patient (Mrs. A) who experienced vertigo and headache. Nursing care is carried out through assessment, diagnosis, intervention, implementation, and evaluation in accordance with SDKI, SIKI, and SLKI. Non-pharmacological interventions in the form of cupping therapy are carried out at specific points according to the patient's complaints, accompanied by education on relaxation techniques and muscle stretching. After cupping therapy and education, the patient's pain intensity decreased from a scale of 5/10 to 2–3/10, the frequency of vertigo attacks decreased, the patient appeared more relaxed, and was able to identify the trigger and perform relaxation techniques independently. The application of nursing care based on SDKI, SIKI, and SLKI with non-pharmacological interventions in the form of cupping therapy effectively helps reduce the intensity of pain and the frequency of vertigo attacks in patients, as well as increase the comfort and independence of patients in managing their complaints.